2012
DOI: 10.12968/bjcn.2012.17.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Timely symptom management at end of life using ‘just in case’ boxes

Abstract: This article discusses the successful implementation of anticipatory prescribing using 'just in case' boxes (JICB) in primary care across the Grampian region and a subsequent follow up survey one year later. The implementation approach used local educational sessions to primary care clinicians. The survey was distributed to 65 primary care bases to gauge awareness and use of the JICB and thoughts about how the box was used. An estimate of prescription costs was undertaken using stock balance forms. The respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…3,5,40 Difficulties are encountered in predicting when patients are likely to die 3,24 with GPs and community nurses frequently recalling situations where drugs were not issued in a timely manner. 3,39,48 Nurses often initiate the process by alerting the GP to a patient’s changing condition and requesting an anticipatory prescription. 5,20,24,37,49 One study reported nursing home staff would request anticipatory prescriptions weeks ahead of need to mitigate the difficulty of timely GP reviews.…”
Section: What Is Current Practice?mentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,40 Difficulties are encountered in predicting when patients are likely to die 3,24 with GPs and community nurses frequently recalling situations where drugs were not issued in a timely manner. 3,39,48 Nurses often initiate the process by alerting the GP to a patient’s changing condition and requesting an anticipatory prescription. 5,20,24,37,49 One study reported nursing home staff would request anticipatory prescriptions weeks ahead of need to mitigate the difficulty of timely GP reviews.…”
Section: What Is Current Practice?mentioning
confidence: 99%
“…The range of views of healthcare professionals towards anticipatory prescribing are reported in 21 studies of community, palliative care, and nursing home nurses, care home staff, pharmacists, GPs, and palliative doctors in limited geographical areas (3 rated as high quality, 13 as medium quality, and 5 as low quality). 3,5,14,19,20,24,3337,39,41,44–46,48,51,52,54,55 The majority of the studies focussed on the views and experiences of nurses. 5,19,20,24,35,36,41 Only two studies explored the views of GPs in detail.…”
Section: What Are the Attitudes Of Community Healthcare Professionals?mentioning
confidence: 99%
“…Nurses consistently report some GPs to be reluctant to prescribe anticipatory medications. 10 , 13 , 15 , 17 Prescribing drugs ahead of need raises safety concerns for GPs. 13 , 16 , 18 The GP remains accountable for the drugs they have prescribed, including strong opioids, which may be in the home for weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of many studies recognise the need for proactive care planning at the end of life 14 , 15 , 18 supporting the aims of anticipatory prescribing to respond to symptoms promptly and prevent hospital admissions that are unwanted by patients. 19 However, until now, the evidence base has primarily been descriptive reports of localised pilots, 20 audits21–23 or guidance and feasibility of use studies. 24 , 25…”
Section: Introductionmentioning
confidence: 99%